(untitled) (Texas Journal of Philology, Culture and History, 2025)
The phenomenon of substantivation—the process by which adjectives function as nouns—plays a significant role in the grammatical and semantic evolution of the English language. This article explores the types, structural features, semantic implications, and syntactic behavior of substantivized adjectives in Modern English. Through analysis of examples from literature, journalism, and colloquial speech, the paper distinguishes between full and partial substantivation and examines the pragmatic functions these forms perform in discourse. A brief comparison with substantivation in other languages is also offered to highlight its universality and unique features in English.